1987
DOI: 10.1111/j.1476-5381.1987.tb11389.x
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of release of endothelium‐derived relaxant factor by manoalide, a potent inhibitor of phospholipase A2

Abstract: 1 The inhibitory action of manoalide on vascular relaxation was characterized. Manoalide was a potent inhibitor ofendothelium-dependent relaxations in the isolated aorta of the rabbit. Responses to acetylcholine (ACh), A23 187 and substance P were reduced by manoalide in a dose-dependent manner whilst those to nitroglycerin were unaffected. 2 Repeated washing of manoalide-treated tissues did not restore the relaxant response to ACh, indicating an irreversible action of manoalide. Scanning electron microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…All of these studies used pharmacological inhibitors to determine the contribution of AA metabolites. A large number of structurally different LO inhibitors, including nordihydroguaiaretic acid (NDGA), phenidone, BW755c, caffeic acid, diethylcarbamazine, AA861, TKM777, cinnanyl-dihydroxy-cyanocinnamate, ebselen, and others (21,33,45,47,50,94,116,146), as well as inhibitors of phospholipases A 2 and C (21,33,46,85,146,153), inhibited relaxations to ACh. Interestingly, inhibitors of CPY also inhibited the endothelium-dependent relaxations to ACh (21,45,116,147).…”
Section: Role Of Lipoxygenase Metabolites Of Aa In Endotheliumdependementioning
confidence: 99%
“…All of these studies used pharmacological inhibitors to determine the contribution of AA metabolites. A large number of structurally different LO inhibitors, including nordihydroguaiaretic acid (NDGA), phenidone, BW755c, caffeic acid, diethylcarbamazine, AA861, TKM777, cinnanyl-dihydroxy-cyanocinnamate, ebselen, and others (21,33,45,47,50,94,116,146), as well as inhibitors of phospholipases A 2 and C (21,33,46,85,146,153), inhibited relaxations to ACh. Interestingly, inhibitors of CPY also inhibited the endothelium-dependent relaxations to ACh (21,45,116,147).…”
Section: Role Of Lipoxygenase Metabolites Of Aa In Endotheliumdependementioning
confidence: 99%
“…7 Moreover, the peptidoleukotrienes LTC 4 and LTD 4 possess the capacity to relax some arterial rings in an endothelium-dependent manner. 8 ' 9 It has also been demonstrated that the decrease in tone in response to ACh and arachidonic acid is attenuated in the presence of SKF525A, an inhibitor of cytochrome P450-dependent monooxygenase.…”
mentioning
confidence: 99%